Kinetic energy-induced growth regimes of nanocolumnar Ti thin films deposited by evaporation and magnetron sputtering. (10th September 2019) - Alvarez, R; Garcia-Valenzuela, A; Rico, V; Garcia-Martin, J M; Cotrino, J; Gonzalez-Elipe, A R; Palmero, A
Abstract: We experimentally analyze different growth regimes of Ti thin films associated to the existence of kinetic energy-induced relaxation mechanisms in the material's network when operating at oblique geometries. For this purpose, we have deposited different films by evaporation and magnetron sputtering under similar geometrical arrangements and at low temperatures. With the help of a well-established growth model we have found three different growth regimes: (i) low energy deposition, exemplified by the evaporation technique, carried out by species with typical energies in the thermal range, where the morphology and density of the film can be explained by solely considering surface shadowing processes, (ii) magnetron sputtering under weak plasma conditions, where the film growth is mediated by surface shadowing mechanisms and kinetic-energy-induced relaxation processes, and (iii) magnetron sputtering under intense plasma conditions, where the film growth is highly influenced by the plasma, and whose morphology is defined by nanocolumns with similar tilt than evaporated films, but with much higher density. The existence of these three regimes explains the variety of morphologies of nanocolumnar Ti thin films grown at oblique angles under similar conditions in the literature.